Penjadwalan Pemeliharaan Trek Kereta dengan Metode Distributed Model Predictive Control - Muhammad Faris; Ircham Ircham (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2019)
This work addresses the development of Distributed Model Predictive Control (DMPC) approaches for the planning of maintenance operations of large-scale railway infrastructure formulated as a Mixed-Integer Linear Programming (MILP) problem. The proposed optimization problem is solved using two different decomposition schemes: Alternating Direction Method of Multipliers (ADMM) and Distributed Robust Safe But Knowledgeable (DRSBK). The original distributed algorithms are modified to handle the non-convex nature of the optimization problem, hence improving the solution quality. The results of large-scale test instances show that DRSBK can outperform the conventional centralized approach and ADMM, by providing the closest-to-optimum solution while requiring the least computation time.